Massage in children with cancer: effectiveness of a protocol - Luís Manuel da Cunha Batalha; Aida A.S.C. Mota (Brazilian Society of Pediatrics, 2013)
Objectives: massage can help relieve pain, although empirical evidence is scarce and contradictory. This study aims to assess the effectiveness of a massage protocol in relieving pain in children hospitalized with cancer. Methods: a randomized, controlled, and single-blind trial was performed in a sample of 52 children aged between 10 and 18 years who were hospitalized in a pediatric cancer ward. The intervention consisted of the implementation of a massage protocol with three sessions of 20 to 30 minutes on alternate days over a one-week period. The effectiveness of the protocol was evaluated by assessing pain using the Brief Pain Inventory (BPI), while the effectiveness of each massage session was measured using the Visual Analogue Scale (VAS). Results: the massage protocol was only effective in reducing the interference of pain in walking (p < 0.05), although it also contributed to relieve pain and its impact on the children's activities. After each massage session, the intensity of the pain experienced by the child decreased (p < 0.001). Conclusions: despite the small sample size, massage therapy appears to be a useful intervention in reducing pain in children with cancer. However, there are still questions regarding the effectiveness of this massage protocol. The authors recommend its use due to its contribution to the promotion of the child's well-being and quality of life.